2020
DOI: 10.3389/fpsyg.2020.00776
|View full text |Cite
|
Sign up to set email alerts
|

Both High Cognitive Load and Transcranial Direct Current Stimulation Over the Right Inferior Frontal Cortex Make Truth and Lie Responses More Similar

Abstract: Deception scholars have argued that increasing the liar's cognitive system artificially can produce deception cues. However, if too much load is imposed, the truth tellers' performance can also be impaired. To address this issue, we designed a veracity task that incorporated a secondary task to increase cognitive load gradually. Also, because deception has been associated with activity in the inferior frontal cortex (IFC), we examined the influence of transcranial direct current stimulation (tDCS) of the IFC o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 77 publications
(103 reference statements)
3
3
0
1
Order By: Relevance
“…Our results may therefore agree with a growing body of literature suggesting that task load is an important factor for consideration in assessing tDCS outcomes (de Almeida, Pope, & Hansen, 2020;Gill, Shah-Basak, & Hamilton, 2015;Meiron & Lavidor, 2013;Sánchez, Masip, & Gómez-Ariza, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Our results may therefore agree with a growing body of literature suggesting that task load is an important factor for consideration in assessing tDCS outcomes (de Almeida, Pope, & Hansen, 2020;Gill, Shah-Basak, & Hamilton, 2015;Meiron & Lavidor, 2013;Sánchez, Masip, & Gómez-Ariza, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Inferior frontal gyrus (IFG) also played a key role in deception in prior reports (Hakun et al, 2008;Kireev, Korotkov, Medvedeva, Masharipov, & Medvedev, 2017;Sánchez et al, 2020;Vartanian et al, 2013). For example, a study conducted by Hakun et al (2008) revealed that IFG activity was predictive of a concealed target during a concealed information task (CIT).…”
Section: Predictability Of Deceptionmentioning
confidence: 99%
“…First, when searching neural activities for deceptive responses, most prior studies directly compared the differences between truth‐telling versus lying conditions. However, the cognitive burden for lying is heavier than that for truth‐telling: lying may require more engagement of working memory, exogenous, endogenous attention, and cognitive control (Sánchez, Masip, & Gómez‐Ariza, 2020 ; Vartanian et al, 2013 ). Usually, when people attempt to lie to a question, they need to intentionally suppress the default truthful response and then make a reverse reaction, which may therefore increase the difficulty of lying.…”
Section: Introductionmentioning
confidence: 99%
“…There have also been several studies of deception using tDCS. Two studies stimulated the right temporo-parietal junction and found decreased deceptive responding in a social context (Tang et al, 2017 ; Noguchi and Oizumi, 2018 ), while most have focused on PFC stimulation (Priori et al, 2008 ; Karim et al, 2010 ; Mameli et al, 2010 ; Fecteau et al, 2013 ; Maréchal et al, 2017 ; Sánchez et al, 2020 ). Priori et al found bilateral stimulation increased reaction time in deceitful responses compared to truth, while Mameli et al, Karim et al, and Fecteau et al found faster RT in lie conditions.…”
Section: Introductionmentioning
confidence: 99%